TREATMENT OF SOLID WASTE (World Science, 2016)
The proposed new energy model is advantageous in that it makes the country's energy system more sustainable, dramatically expanding the raw material base of energy, solves the problem of accumulated waste, and, most importantly, makes rely on its own scientific and technical potential. Energy development in this way makes really innovate widely introduce new technologies, improve and develop them. Such a development would require a rapid revival of energy and mechanical engineering industries, as well as related industries. Develop and implement a plan for the reconstruction of power in accordance with the above proposals would lead to enormous changes in the industry and the economy. Exhaust experience of energy development on a new path can be replicated in other countries and export related to the described methods of energy recycling equipment. This could be a long-term basis to strengthen the country's energy policy.